PENGARUH KONSUMSI KOPI TERHADAP KEJADIAN DIABETES MELITUS TIPE 2 (Studi Follow up Gangguan Toleransi Glukosa di Depok Jawa Barat Tahun 2001-2008) - Ekowati Rahajeng (PERSATUAN AHLI GIZI INDONESIA, 2010)
EFFECT OF COFFEE CONSUMPTION FOR THE INCIDENCE OF TYPE 2 DIABETES MELLITUS(Follow up Study for Impaired Glucose Tolerance in Depok, West Java 2001-2008)Coffee consumption is known to increase the risk of the incidence of Type 2 Diabetes Mellitus. Effect of coffee consumption on the occurrence of Type 2 diabetes has been investigated in 289 cases of impaired glucose tolerance (IGT) through prospective cohort studies since 2001 in Depok City, West Java. Coffee drinking habits was collected through measure of caffeine content were consumed. Caffeine content was measured by Atomic Absorption Spectrophotometer (AAS) using the method High Performance Liquid Chromatography (HPLC). Diagnosis of IGT determined based on examination results of fasting blood glucose levels ie lower 126 mg / dL and 2 hours after 75 g glucose load blood glucose levels ie 140-199 mg / dL. Diagnosis of diabetes melitus determined by the basis of the results of clinical examination and results of fasting blood glucose levels, ie ≥ 126 mg / dL and/or results of blood glucose 2 hours after glucose load, ie ≥ 200mg/dl. The follow-up study, to confirm these effects was conducted in 2008. Multinomial logistic multivariate analysis of coffee consumption habits and all variables equally harmful risk of incident type 2 diabetes suggests that coffee consumption with caffein content of 240-359,9 mgcaffein had high risk of type 2 diabetes with RR value 3.88 (95% CI 1.20, 8.75), and RR for coffee consumption with caffein content = 360 mg caffein daily was 5.46 (95% CI 1.57, 11.86). Another factors was contribut to the incidence of type 2 diabetes mellitus is high fat consumption with RR 4.64 (95% CI 1.90, 10.28), obesity with RR 4.04 (95% CI 1.31, 8.27 ), and hypertriglyceride with RR 4.99 (95% CI 1.55, 10.19). High fiber consumption, and high physical activity was found to prevent Type 2 diabetes with RR 0.37 (95% CI 0.10, 0.70) and RR 0.42 (95% CI 0.18, 0.68).Keywords: coffee consumption, type 2 Diabetes Mellitus